Cocrystals of ciprofloxacin with nicotinic and isonicotinic acids: Mechanochemical synthesis, characterization, thermal and solubility study - de Almeida, Amanda Cosmo [UNESP]; Torquetti, Carolina [UNESP]; Ferreira, Patrícia Osório [UNESP]; Fernandes, Richard Perosa [UNESP]; dos Santos, Everton Carvalho [UNESP]; Kogawa, Ana Carolina [UNESP]; Caires, Flávio Junior [UNESP] (Elsevier, 2020)
This article describes the synthesis and characterization of new cocrystals of ciprofloxacin with nicotinic and isonicotinic acids as coformers. The cocrystals were obtained by a mechanochemical method (neat and liquid-assisted grinding). The characterization of the cocrystals was carried out using differential scanning calorimetry (DSC), thermogravimetry and simultaneous differential thermal analysis (TG-DTA), infrared spectroscopy (IR), and powder X-ray diffractometry (PXRD). Using these thermal, spectroscopic and diffractometric methods it was possible to verify the formation of the cocrystals, either with or without the addition of ethanol. Additionally, binary phase diagrams, constructed from the data of the DSC curves, confirmed the formation of the cocrystals and their stoichiometry; 1:1 (mol/mol) was determined as the optimal stoichiometric ratio. Furthermore, the formed cocrystals were capable of improving the aqueous solubility of the bioactive agent used in this study.
Keywords: Ciprofloxacin; Cocrystal; Mechanochemical synthesis; Solubility study; Thermal analysis